Antibiotic Prescriptions for Upper Respiratory Infections in a Pediatric Office Versus an Urgent Care Center. (March 2019) - Hayes, Rebecca; Merritt, Brandon; Lewis, Stacee; Shields, Jessie; Gerlach, Jennifer; Gress, Todd W.; Evans, Joseph
It is estimated that as many as 10 million unnecessary antibiotic prescriptions are written each year for children. Children are more likely to receive antibiotics for an upper respiratory infection in an urgent care center compared with the primary care office. However, no study has examined the antibiotic prescribing practices of the same physicians in these settings. This retrospective chart review evaluated pediatricians' antibiotic prescribing practices for patients with symptoms of an upper respiratory tract infection in the office setting and an urgent care setting. There was no difference in the total antibiotic prescribing rate by pediatricians in their primary care office versus an urgent care setting. Pediatricians who were high antibiotic prescribers in the office setting were also high prescribers in the urgent care. The highest prescribing physicians prescribed the appropriate recommended antibiotics for a particular diagnosis the lowest percentage of the time. Efforts to promote antimicrobial stewardship should be directed toward the individual physician and not toward the location where the patients are being evaluated.